El "status" socio-académico de las matemáticas : un punto de referencia singular - Arana Pérez, J.; Escudero Escorza, Tomás; Garces Campos, R.; Palacian Gil, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Results of different surveys among students of basic and secondary education show that mathematics are perceived as a subject -matter with special status, as compared with the rest of disciplines; its importance, academic utility, difficulty and boredom are emphasized. This panorama changes a little according to educational levels, kind of studies, courses and so on, but the differenciated socio -academical status persists.